Traction Dynamics Using Automatic Transmission Combined with Torque Converter - Duc Lich Luu; Sy Dong Ngo (Journal of Technical Education Science, 2025)
The paper studies the longitudinal dynamic model of a car using a hydraulic transmission system combined with an automatic transmission. This model includes an internal combustion engine, a hydraulic torque converter, a geared automatic transmission, a main transmission, a semi-axle and a wheel, under the influence of resistance forces such as air resistance, inertia, rolling resistance and uphill resistance. Calculations are performed to determine the structural parameters of the transmission system and the engine, thereby evaluating the vehicle’s ability to overcome resistance during movement. The paper also applies analytical and simulation methods to calculate the traction dynamics of the automatic transmission system. The results obtained from the simulation include graphs of traction force, dynamic factors and acceleration of the car, thereby evaluating the vehicle’s ability to overcome resistance, acceleration, climbing and maintaining speed. The results obtained will serve as the basis for determining the vehicle’s ability to work under specific practical conditions.